The new dynamic public finance - Kocherlakota, Narayana Rao, 1963- (Toulouse lectures in economics., 2010)
Optimal tax design attempts to resolve a well-known trade-off: namely, that high taxes are bad insofar as they discourage people from working, but good to the degree that, by redistributing wealth, they help insure people against productivity shocks. Until recently, however, economic research on this question either ignored people's uncertainty about their future productivities or imposed strong and unrealistic functional form restrictions on taxes. In response to these problems, the new dynamic public finance was developed to study the design of optimal taxes given only minimal restrictions on the set of possible tax instruments, and on the nature of shocks affecting people in the economy. In this book, Narayana Kocherlakota surveys and discusses this exciting new approach to public finance. An important book for advanced PhD courses in public finance and macroeconomics, The New Dynamic Public Finance provides a formal connection between the problem of dynamic optimal taxation and dynamic principal-agent contracting theory. This connection means that the properties of solutions to principal-agent problems can be used to determine the properties of optimal tax systems. The book shows that such optimal tax systems necessarily involve asset income taxes, which may depend in sophisticated ways on current and past labor incomes. It also addresses the implications of this new approach for qualitative properties of optimal monetary policy, optimal government debt policy, and optimal bequest taxes. In addition, the book describes computational methods for approximate calculation of optimal taxes, and discusses possible paths for future research.